2020
DOI: 10.1103/physrevb.101.094303
|View full text |Cite
|
Sign up to set email alerts
|

Transient three-dimensional structural dynamics in 1TTaSe2

Abstract: We report on thermal and optically driven transitions between the commensurate (C) and incommensurate (IC) charge-density wave (CDW) phases of 1T-TaSe 2. Optical excitation results in suppression of the C-CDW on a subpicosecond timescale. The optically driven C to IC transition involves a short-lived (∼1 ps) unreconstructed phase. Nucleation of an IC phase stacking order is observed already at ∼4 ps following photoexcitation. The short timescales involved in establishing the stacking order implies that the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Sometimes confined systems, such as these 2D CDW materials, are subjected to conditions that may bring about a 3D-like nature. Such was the case in Ji et al [ 166 ], who reported on the optical suppression of the C-CDW over a sub-ps timescale. The group claims that the short timescales involved in establishing the stacking order implies that the nucleation of the IC-CDW phase is inherently of a 3D nature.…”
Section: Effects Of Confinement and Dimensionalitymentioning
confidence: 75%
See 1 more Smart Citation
“…Sometimes confined systems, such as these 2D CDW materials, are subjected to conditions that may bring about a 3D-like nature. Such was the case in Ji et al [ 166 ], who reported on the optical suppression of the C-CDW over a sub-ps timescale. The group claims that the short timescales involved in establishing the stacking order implies that the nucleation of the IC-CDW phase is inherently of a 3D nature.…”
Section: Effects Of Confinement and Dimensionalitymentioning
confidence: 75%
“…The simulated diffraction patterns are shown along [001] ( e ) and [102] ( h ). Reference [ 166 ] is an open-access article distributed under the terms of the Creative Commons CC BY ( (accessed on 14 December 2021)) license, which permits unrestricted use, distribution, and reproduction in any medium.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, observation of CAP d-spacing oscillations (Fig. 3c) is uncommon despite PLDs having large-amplitude LA-mode character consisting of significant basal-plane atomic modulations (8,40,(61)(62)(63)(64)(65). As seen in Figure 3c, both Bragg-scattering parameters display anomalous behavior for t < ~75 ps.…”
Section: Resultsmentioning
confidence: 93%
“…3c) is uncommon despite PLDs having large-amplitude LA-mode character consisting of significant basal-plane atomic modulations. 8,40,55,[63][64][65][66] Despite this, subpicometer d-spacing changes are indeed generally observable with UEM. 40,67,68 Most interestingly, as seen in Figure 3c, both Bragg-scattering parameters display anomalous behaviors for t < ~75 ps.…”
Section: )mentioning
confidence: 99%